Performance and carcass characteristics of cattle with different castration practices - M. M. Anjos; V. S. Miler; B. N. Barboza; E. O. Queiroz; B. R. C. N. Pazdiora; G. A. Viana; R. D. Pazdiora (Boletim de Indústria Animal)
The aim of this research was to evaluate the performance and carcass characteristics of immunocastrated cattle, in comparison to castrated and non-castrated cattle supplemented on pasture. 36 bovines were used, distributed in a completely randomized design, in 3 treatments: non-castrated animals (ANC), animals castrated late by the surgical method (ACC) and immunocastrated animals (AIC), with 12 replicates each. Immunocastration was performed following the protocol of two doses of the immunocastrating vaccine, with an interval of 60 days, promoting a castrated effect of 120 days. The animals were kept on mixed pasture in an extensive rearing system using rotational grazing, they received mineral supplement in the first 3 months and specific feed for the fattening season in the subsequent 3 months, according to the property’s standards. The total experimental period was 180 days. Data were hidden from the normality test, analysis of variance and mean comparisons were performed using the Tukey test, except for the variable degree of finishing, which was maintained at the chi-square test, at 5%. Average daily weight and total weight gains, hot and cold carcass weights and hot and cold carcass yield did not show statistical differences (P>0.05) for animals submitted to different treatments. However, the cooling loss was lower in immunocastrated animals (P<0.05), followed by surgically castrated and non-castrated animals. Immunocastrated and surgically castrated animals showed better carcass finishing (P<0.05) than non-castrated animals. The initial temperature of the carcass was lower (P<0.05) in the immunocastrated group, while for the final temperature no statistical differences (P>0.05) were verified for the animals submitted to different treatments. Final carcass pH was higher (P<0.05) in immunocastrated than in surgically castrated animals, but did not differ (P>0.05) from non-castrated animals. Immunocastrated animals, in a grazing system receiving supplementation, showed similar gains in weight and carcass weight in relation to non-castrated and surgically castrated animals, however, with lower losses to carcass cooling.